Technical report: fundamental study of Adomian Decomposition Method in solving prey-predator model / Hazmi Abu Yazid, Muhammad Salihin Zamri and Mohamad Nazrul Iman Mohamad - Abu Yazid, Hazmi; Zamri, Muhammad Salihin; Mohamad, Mohamad Nazrul Iman (2016)
Lotka-Volterra model which is in the form of system of ordinary differential equations is the most famous mathematical model used in simulating the relation between a prey and a predator. The trends of solutions of the model differs as the value of parameters used in the equations differs, hence may effect the accuracy of the model's solution. Among identified parameters involved in Lotka-Volterra model are death rate, eaten rate and born rate. The purpose of this project is to study two-species interactions using Lotka-Volterra equations. Adomian Decomposition Method is employed to approximate solutions of the system of nonlinear Volterra differential equations governing on the problem. Hence the best parameters used in simulating the prey-predator relation are identified and selected. All in all, the above mentioned results are important to be observed and studied in order to understand the ecological interactions between prey and predator populations.